Stereotactic aspiration for hypertensive intracerebral haemorrhage in a Chinese population: a retrospective cohort study. Issue 1 (2nd March 2019) - Zhang, Xuyang; Zhou, Shaolong; Zhang, Qiang; Fu, Xudong; Wu, Yuehui; Liu, Jiasheng; Liang, Bo; Yang, Zhuo; Wang, Xinjun
Abstract : Objective: We aimed to compare the therapeutic effects of stereotactic aspiration and best medical management in patients who developed supratentorial hypertensive intracerebral haemorrhage (HICH) with a volume of haemorrhage between 20 and 40 mL. Methods: The clinical data of 220 patients with supratentorial HICH with a volume between 20 and 40 mL were retrospectively analysed. Among them, 142 received stereotactic aspiration surgery (stereotactic aspiration group) and 78 received best medical management (conservative group). All were followed up for 6 months. Multivariate logistic regression and Kaplan-Meier survival curves were used to compare the outcome between the two groups. Results: The rebleeding rate was lower in the group that had stereotactic aspiration when compared with the group with medical treatment (6 [4.2%] vs 9 [11.5%], χ 2 =4.364, p=0.037). After 6 months, although the mortality rate did not differ significantly between the two groups (8 cases [5.6%] vs 10 cases [12.8%], χ 2 =3.461, p=0.063), the rate of a favourable outcome was higher in the group who received stereotactic aspiration (χ 2 =15.870, p=0.000). Logistic regression identified that medical treatment (OR=1.64, p=0.000) was an independent risk factor for an unfavourable outcome. The Kaplan-Meier curves indicated that the median favourable outcome time in the stereotactic aspiration group was 59.5 days compared with that in the medically treated group (87.0 days). The log-rank test indicated that the prognosis at 6 months was better for those treated with stereotactic haematoma aspiration (χ 2 =29.866, p=0.000). However, the 6-month survival rate was similar between the two groups (χ 2 =3.253, p=0.068). Conclusions: Stereotactic haematoma aspiration significantly improved the quality of life, although did not effectively reduce the rate of mortality. When selected appropriately, patients with HICH may benefit from this type of surgical intervention.